Women and globalization: victims, sites of resistance and new world views - Ruether, Rosemary Radford (Mandrágora, 2025)
My theme for this essay is "Women and Globalization." I wish to talk about women's relation to globalization both in the ways that women, especially poor women, are disproportionately victims of globalization, and also the way in which women, or women's groups, are among the important sites of critique and resistance to globalization. I also want to suggest some ways in which altemative movements and worldviews of the Sacred are emerging from this struggle.